179k views
3 votes
Need answers quickly need it step by step

(−5)2 −2×(−9)+6=

(−9)−(−8)+2×42=

8÷(−4)×(−6)2 +7=

10×5−(−6)2 +(−8)=

(10 ÷ (−5) − (−2)) × (−3)3=

3×10+8−42=

(−3)3 −2+8÷(−8)=

4×(−8)+6−(−2)3=

(−5)2 ×3÷5+9=

4 × (−6) ÷ 8 + 33=

Thanks

1 Answer

5 votes

Answer:

Explanation:

1. -10+18+6=8+6=14

2. -1+84=83

3. -2×(−6)2 +7=12×2+7=24+7=31

4. 50-(−6)2 +(−8)=50+12-8=62-8=54

5. (-2+2)× (−3)3=0× (−3)3=0

6. 30+8-42=38-42=-4

7. -9-2-1=-12

8. -32+6+6=-20

9. -10×3÷5+9=-30÷5+9=-6+9=3

10. -24÷ 8 + 33=-3+33=30

User AndyHu
by
5.7k points